If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+3*2=6
We simplify the equation to the form, which is simple to understand
4x+3*2=6
We move all terms containing x to the left and all other terms to the right.
+4x=+6-6
We simplify left and right side of the equation.
+4x=0
We divide both sides of the equation by 4 to get x.
x=0
| P=5-15m | | 11x+7y=141 | | 9z+3=3 | | 8x^2+16x-42=y | | 2r+3k-5=-7 | | 14x+12=5y | | 14-l+3k-6= | | 2x+6=(3x-2)-(x+4) | | 14x+14=9x+54 | | 30x+20=150 | | -8.9=1.1-5y | | 13m-6+n-1= | | 14x-14=9x+54 | | (9x+4)(9x+4)= | | 11n+3+7-2m= | | -108+-9x=-16x+-80 | | B(n)=25*0.9n | | 8y-z-3= | | 4x^2+8x-194=0 | | 3(x+5)+2x=8 | | 0.06(6t-5)=0.36(t+5)-2.10 | | 2(w-1)-2=-4(-6w+3)-4w | | 3(t+9)=18 | | 12d-4c+7= | | 0.3x+1.3=0.7x-2.3 | | -108+-9x=-16+-80 | | 5+2k=-17 | | C(n)=5+n | | -0.6x^2-2=-5 | | -12=6 | | 12x^2-80x-96=0 | | 6x-17=x+11 |